School attendance and school absenteeism: A primer for the past, present, and theory of change for the future - Kearney, Christopher A.; Benoit, Laelia; Gonzálvez, Carolina; Keppens, Gil (Frontiers in Education, 2022)
School attendance and school absenteeism have been studied for over a century, leading to a rich and vast literature base. At the same time, powerful demographic, climate, social justice/equity, and technological/globalization forces are forcing disparate stakeholders worldwide to quickly adapt to rapidly changing conditions and to consider new common visions of child education for the next century. These overarching forces are utilized within a theory of change approach to help develop such a vision of school attendance/absenteeism for this era. This approach adopts key long-range outcomes (readiness for adulthood for all students; synthesized systemic and analytic approaches to school attendance/absenteeism) derived from thematic outputs (reframing, social justice, shared alliances) that are themselves derived from contemporary inputs (movement of educational agencies worldwide toward readiness for adulthood, technological advances, schools and communities as one). As with theory of change approaches, the purpose of this discourse is not to provide a roadmap but rather a compass to develop multi-stakeholder partnerships that can leverage shared resources and expertise to achieve an eventual final common goal.